Analysis of Students’ Difficulties In Reading Texts to Increase Reading Comprehension In Islamic Senior High School - Fadilatur Rohma; Achmad Fawaid (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
One of the student's difficulties in reading Arabic texts, in general, is due to the unique shape of the Arabic letters and no resemblance to the alphabet. So that students feel foreign in identifying and recognizing the letters. Therefore, this study aims to analyze the difficulty of reading Arabic texts in maharah qira'ah learning, starting from linguistic, and non-linguistic problems, and providing solutions to Arabic subject teachers in overcoming these difficulties. The method used is a qualitative approach. The technique used is to use data collection, in collecting data for this study, namely by interviews, observation, and documentation. The research uses this technique because it is done by listening or observing the reading of Arabic texts in maharah qira'ah. And this technique is used to observe the speech of students who are carried out at Madrasah Aliyah Al-Barokah, especially Class X IPS. The difficulty of students reading Arabic texts in learning maharah qira'ah there are two influencing factors, namely internal factors (linguistics) and external factors (non-linguistics). The results of the study indicate that there are two factors for difficulty reading Arabic texts, namely internal factors (linguistics) and external factors (non-linguistics). And the efforts that must be made by an educator in overcoming students' difficulties in reading Arabic texts are by getting used to speaking Arabic even if only a little, providing motivation, giving rewards, getting used to reading Arabic texts, and changing the views of students who think that learning Arabic is difficult and not interesting, learning becomes easy and interesting